DESIGN AND DEVELOPMENT OF AN ELECTRIC BIKE (International Journal of Food and Nutritional Sciences, 2021)
The electrically assisted electric bicycle's function is to give an existing bicycle electromagnetic momentum. This frees the rider from having to provide the energy needed for the bicycle to function as intended. With just a little charging time, its powerful motor and large battery capacity enable it to assist with incline climbing, accelerate driving, and give entirely free electric transportation. It is our duty to minimize the quantity of fuel utilized and the potentially harmful effects of its burning on the environment. All things considered, it is a tiny step in the direction of lowering the usage of fuel-intensive cars and raising awareness of alternatives to these modes of transportation, such electricbikes. Therefore, we propose to develop a battery-powered bike instead of an electric bike. This type of bike is referred to as "battery-operated." This bike would require less effort from a human rider. Search terms to look for include battery, fabrication, and electric bike.